2019
DOI: 10.1111/1471-0307.12601
|View full text |Cite
|
Sign up to set email alerts
|

Effects of curd heating with or without previous milk pasteurisation on the microbiological quality and safety of craft‐made ‘Pasta Filata’ Kashkaval cheese curds

Abstract: An empirical ‘Pasta Filata’ process used for traditional Kashkaval cheese manufacture from raw ewes’ milk improved the hygiene of fresh curd. Coagulase‐positive (RPF+) staphylococci and coliforms declined by 2.4 and 4.5 log units, respectively, and Listeria contamination was minimised. Before Pasta Filata, RPF+ staphylococci exceeded the 5‐log threshold level specified in EC Regulation 1441/2007 in raw milk curds despite the prevalence of indigenous mesophilic lactic acid bacteria. Pasta Filata favoured entero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…Total staphylococcal colonies, Enterobacteriaceae, coliforms and yeasts-moulds of kashkaval of Pindos cheese were at low levels at all sampling dates (data not shown). The use of pasteurized milk and the heat treatment of the curd during texturizing possibly had a preservative effect on kashkaval of Pindos cheese, which is in agreement with the results of Pappa et al [ 3 ] and Samelis et al [ 4 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Total staphylococcal colonies, Enterobacteriaceae, coliforms and yeasts-moulds of kashkaval of Pindos cheese were at low levels at all sampling dates (data not shown). The use of pasteurized milk and the heat treatment of the curd during texturizing possibly had a preservative effect on kashkaval of Pindos cheese, which is in agreement with the results of Pappa et al [ 3 ] and Samelis et al [ 4 ].…”
Section: Resultssupporting
confidence: 92%
“…In previous studies, the seasonal (usually during summer, at the end of the lactation period) manufacturing process of kashkaval of Pindos and Urda farmhouse cheeses made in small artisanal units using traditional technology and simple processing equipment in the mountains was described [ 3 , 4 , 5 ]. The present work was conducted to complement the previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Staphylococcal food poisoning is the result of consuming foods containing sufficient amounts of its enterotoxins, with food borne outbreaks of S. aureus intoxication's been associated with the consumption of contaminated milk and dairy products in many countries ( (Saka & Terzi Gulel, 2018). In addition, microbiological analysis of raw milk cheese revealed varying degrees of quality and safety, with Staphylococcus aureus considered a potential food enterotoxin-producing species (Samelis et al, 2019). Also, it has been shown that coagulase negative staphylococcus (CNS) may be involved in food poisoning because they can also carry enterotoxin encoding genes (se genes) in their genomes that they are thermoresistant (Samelis et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, microbiological analysis of raw milk cheese revealed varying degrees of quality and safety, with Staphylococcus aureus considered a potential food enterotoxin-producing species (Samelis et al, 2019). Also, it has been shown that coagulase negative staphylococcus (CNS) may be involved in food poisoning because they can also carry enterotoxin encoding genes (se genes) in their genomes that they are thermoresistant (Samelis et al, 2019). The Staphylococcus spp enterotoxin (SE) genes are encoded in mobile genetic elements, such as plasmids, prophages, and pathogenic islands that are able to be transmitted though S. aureus strains even during food processing (Cardoso & Marin, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The traditional cheese-making technology of Kashkaval cheese has been recorded since the beginning of the previous century (Dimitriadis, 1900;Liambeis, 1900;Polychroniadis, 1912) and the biochemical characteristics of the artisanal cheese have been studied before (Pappa et al, 2019;Samelis et al, 2019). The aim of the present work was a) to study the effect of the salting methods that are commonly used in its manufacture by the different cheese-makers and b) to provide some historical data regarding the Kashkaval of Pindos cheese.…”
Section: Introductionmentioning
confidence: 99%